Remote Sensing Study of the Impact of Social-Economic Development on The Scale of Land Use in The Shaki District - Nofal Artunov (LAFADZ JAYA Publisher, 2023)
The study investigates the changes in both the quantity and quality of land use in the Shaki district resulting from the increased level of social and economic development. Remote sensing was used to analyze the projects implemented under the State program 'Social and Economic Development of Regions,' assessing their impact on land use. The projects were categorized as either 'changing' or 'replacing,' based on their degree of impact, scale, and transformations between areas. The study also examined the population distribution by altitude zones and settlement levels. The satellite images were decoded and the land use areas were divided into classes. The level of land use between 2001 and 2020 was analyzed using the support vector machine (SVM) method to calculate the scale, difference, and regional growth rate of individual areas. The changes that occurred were identified and explained. Additionally, the transitions between categories were studied, the main changing and expanding areas were identified, and the increasing and decreasing tendencies between classes were examined.